Perancangan Sistem Informasi Sensus Penduduk Berbasis Android Pada Desa Meranti - Listia, Bella Ayu; Purnama, Iwan; Harahap, Syaiful Zuhri (Universitas Labuhanbatu, 2020)
Population census information system that can facilitate the recording of population census data so that accurate and timely results can be obtained by testing the black box testing system. The purpose of this study is to design / create a population census information system that can facilitate the recording of population census data so that accurate and timely results can be obtained. The benefits of this study is that this system can facilitate and assist employees who are in the Meranti village head office so that the recording of population census data obtained accurate and timely results.